Learners’ Blended Learning Experience at Osias Colleges Incorporated - Castro, Rein Mark F.; Balibat, Aurora M.; Osongco, Robert E.; Ramos, Roger P.; Solis, Dulce Marie B. (Future Science / FSH-PH Publications, 2025)
This study utilized a descriptive research design to explore learners' experiences and challenges in blended learning at Osias Colleges Incorporated. It involved 248 students selected via convenience sampling and uses a researcher-developed questionnaire, validated by experts and pilot-tested with a Cronbach's alpha of 0.90, serves as the primary data collection tool. The study assessed learners' profiles and their blended learning experiences across engagement, flexibility, instruction quality, technical support, and collaboration. It also identified challenges and opportunities for improvement to enhance the program's effectiveness, using frequency, percentages, and mean for data analysis. Most respondents in the study are first-year college students pursuing a Bachelor of Science in Criminology. Overall, learners at Osias Colleges Incorporated report a positive experience with the blended learning modality. However, respondents identified significant challenges, including technical issues like software glitches and connectivity problems, as well as the need for personalized support. Opportunities for improvement are centered around five key components of blended learning: students' engagement, flexibility, quality of instruction, technical support and accessibility, and collaboration, all of which are intertwined with the challenges faced by learners. To enhance the blended learning at Osias Colleges Incorporated, several strategies can be implemented. Incorporating interactive multimedia resources like videos, quizzes, and simulations can boost learner engagement. Implementing an accessible technical support system will address software and connectivity issues promptly. Finally, regularly assessing and refining the five key components of blended learning—engagement, flexibility, instruction quality, technical support, and collaboration—will ensure a more effective learning environment by addressing challenges proactively.